Banjar Wayang Kulit As A Media For Implementing The Profile of Pancasila Students Aspects of Working Together - Muhammad Rico; Dewicca Fatma Nadilla (Amandemen: Journal of Learning, Teaching and Educational Studies, 2024)
The first aim of writing this article is to analyze the background to the implementation of Banjar Shadow Puppetry. The second objective is to analyze efforts to implement the Pancasila Student Profile through the implementation of Banjar Shadow Puppets. The third objective is to analyze the impact of implementing Banjar Shadow Puppets as a medium for implementing the Pancasila Student Profile aspect of Gotong Royong. This research uses the literature study method, which is an activity that is required in research, especially academic research whose main aim is to develop theoretical and practical aspects and temporary conjectures in research. The results of the research show that the background to the implementation of Banjar shadow puppetry is because of circumcision events, inauguration ceremonies, weddings, national holidays or to fulfill someone's vows. Efforts to implement the Pancasila student profile in Banjar shadow puppetry can be seen from these figures who have exemplary examples that can be applied in social life. The impact of implementing Banjar shadow puppetry also has a connection and there are values contained in it from the beginning of the activity until the end. Activities require mutual cooperation from elements of society. This can be an example in its application at school.